DNA Computing: Principle, Construction, and Applications in Intelligent Diagnostics. Issue 11 (8th August 2021) - Ma, Qian; Zhang, Chao; Zhang, Mingzhi; Han, Da; Tan, Weihong
Abstract : Demands on faster information processing speed and denser data storage are catalyzing new computation modes. DNA, as an important biomolecule that carries genetic information, has shown its potential in information processing and storage due to its predictable base pairings and nanoscale size for programmable and high‐throughput coding, as well as computing. More importantly, DNA also plays key biological roles, including regulating gene expression and monitoring biochemical reactions in the cells. When these capabilities are combined, the result is the development of new fields of DNA computing in biology and biomedicine. Herein, the most recent and important developments in DNA‐based computing for biomedical applications are presented, mainly from the perspective of biosensing related to diagnostics. The design and implementation of DNA computing systems from all stages in the pipeline are also discussed. The aim is to present DNA computing as a serious tool for intelligent diagnostics. Abstract : DNA computing can integrate the functions of nucleic acids as biomolecules that recognize biomarkers with their ability to analyze and perform computational functions, which provides a general and modular framework for intelligent diagnostics. Herein, the construction of intelligent DNA computing systems and their applications in diagnostics are focused on.